Differences in Occurrence, Risk Factors and Severity of Early-onset Atopic Dermatitis among Preterm and Term Children - Trine Gerner; Maria Rasmussen Rinnov; Anne-Sofie Halling; Nina Haarup Ravn; Mette Hjorslev Knudgaard; Caroline Ewertsen; Simon Trautner; Ivone Jakasa; Sanja Kezic; Lone Skov; Jacob P. Thyssen (Medical Journals Sweden, 2022)
This prospective birth cohort followed 150 preterm and 300 term newborns during the first year of life to assess possible differences in risk factors, age at onset, anatomical location, and severity of atopic dermatitis. Atopic dermatitis was diagnosed clinically, and severity was assessed using Eczema Area Severity Index (EASI). DNA was analysed for filaggrin gene mutations. Parents were asked about environmental exposures and emollient use. Atopic dermatitis during the first year of life was observed in 21.2% of children and was more common in term children compared with preterm children (26.7% vs 11.7%, p < 0.001), with lower age of onset (4 vs 6 months, p < 0.05) and more severe disease at onset (EASI: 4.8 vs 0.4, p < 0.0005). Environmental risk factors for atopic dermatitis were essentially similar for preterm and term born children, apart from winter and autumn births. Filaggrin gene mutations were less common in preterm than term children (4.1% vs 9.2%, p = 0.06).